E-Portfolio's Impact on Writing Abilities (A Case Study on Second Semester Students of English Education) - Fasa, Raden Hasby Isnaindy (English Language Education, Universitas Internasional Batam, 2023)
This study aimed to explore the utilization of Wattpad as an E-Portfolio platform in teaching writing and assess the improvements in students' writing qualities. This study took a qualitative approach and used a case study design. Ten students from the English Education Department in Bandung, West Java, took part in the experiment. The data were gathered through observations to determine the process of developing students' writing ability through the E-Portfolio platform, as well as examination of students' writing to determine students' writing ability improvement. The purpose of the writing analysis was to examine how students improved during the writing activities, which was reflected in their writing from the first to the third writing. The result showed that the use of E-Portfolio Platform was not only increased the students’ participation and motivation to actively involved in the writing process but also improved students’ writing ability. The findings suggest that incorporating such platforms in educational settings can positively impact students' engagement and motivation, leading to improved writing skills. Educators and institutions can consider integrating E-Portfolio platforms into their curriculum to enhance student learning outcomes in writing.